Money matters in migration : policy, participation, and citizenship - Lange, Tesseltje de; Schrauwen, Annette; Maas, Willem, 1972- (Cambridge : Cambridge University Press, 2021)
Migration, participation, and citizenship, are central political and social concerns, are deeply affected by money. The role of money - tangible, intangible, conceptual, and as a policy tool - is understudied, overlooked, and analytically underdeveloped. For sending and receiving societies, migrants, their families, employers, NGOs, or private institutions, money defines the border, inclusion or exclusion, opportunity structures, and equality or the lack thereof. Through the analytical lens of money, the chapters in this book expose hidden and sometimes contradictory policy objectives, unwanted consequences, and inconsistent regulatory structures. The authors from a range of fields provide multiple perspectives on how money shapes decisions from all actors in migration trajectories, from micro to macro level. Taking an interdisciplinary approach, the book draws on case studies from Europe, the Americas, Asia, and Africa. This comprehensive overview brings to light the deep global impacts money has on migration and citizenship.
Title from publisher's bibliographic system (viewed on 24 Nov 2021).
Keywords: Emigration and immigration -- Economic aspects; Political rights; Citizenship -- Economic aspects; Emigration and immigration -- Government policy